The Influence of Viral Marketing and Customer Trust toward Customer Purchase Intention of Xiaomi Smartphone in Manado - Alfian Jeremmy Sanggamele; James D.D. Massie; Fitty V. Arie (Universitas Sam Ratulangi, 2022)
Smartphone is a mobile phone or smart cellular phone that is equipped with the latest features and high capabilities like a computer. Smartphone market competition is increasing, it is undeniable that the use of smartphones among the community has become a necessity to support activities such as work or school, especially in the midst of the COVID-19 pandemic. The objectives of this study are To Know the Viral marketing and Customer Trust toward Customer Purchase Intention of Xiaomi Smartphone in Manado. The analytical method used is Multiple linear regression. Based on the results of the analysis and discussion using Multiple linear regression and classical assumption test, it is concluded that the results of the hypothesis test found that simultaneously Viral Marketing and Customer Trust had a significant effect on Customer Purchase Intention. For Xiaomi Smartphone to maintain and improve the quality of brand again so that it will make its consumers more loyal to the brand also satisfied.